2021
DOI: 10.3390/children8020079
|View full text |Cite
|
Sign up to set email alerts
|

New Parents Experienced Lower Parenting Self-Efficacy during the COVID-19 Pandemic Lockdown

Abstract: Background: The COVID-19 pandemic is a global issue which affects the entire population’s mental health. This study evaluates how restrictions to curtail this pandemic change parenting self-efficacy, depressive symptoms, couple satisfaction and health-related quality of life in parents after delivery of a newborn. Methods: In this prospective single center evaluation of parental self-efficacy and quality of life, four validated questionnaires were used to repeatedly assess parenting self-efficacy (Tool to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 40 publications
3
30
0
2
Order By: Relevance
“…Individuals who required access to routine medical services such as pregnant women and people with chronic conditions experienced mental health issues such as stress, depression and reduced emotional well-being [14][15][16][17]. The emotional well-being of parents and children also suffered due to the lack of educational and food resources and the enhanced stress and financial problems due to restricted and insufficient healthcare facilities, especially in less-developed countries [18][19][20][21][22]. Due to the overwhelming number of positive cases and the limited availability of medical devices, the pressure on healthcare workers (HCWs) has significantly increased and placed them at higher risk of contracting the contagion.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who required access to routine medical services such as pregnant women and people with chronic conditions experienced mental health issues such as stress, depression and reduced emotional well-being [14][15][16][17]. The emotional well-being of parents and children also suffered due to the lack of educational and food resources and the enhanced stress and financial problems due to restricted and insufficient healthcare facilities, especially in less-developed countries [18][19][20][21][22]. Due to the overwhelming number of positive cases and the limited availability of medical devices, the pressure on healthcare workers (HCWs) has significantly increased and placed them at higher risk of contracting the contagion.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 679 relevant references were identified in the literature search, and 634 studies were excluded through screening of titles and abstracts. This left 45 papers for full-text screening, of which 16 were excluded: data for postpartum women were not reported separately in nine studies ( Li et al, 2021 ; Masters et al, 2021 ; Perzow et al, 2021 ; Wang et al, 2021 ; Liu et al, 2021 ; Stepowicz et al, 2020 ; Xue et al, 2021 ; Chaves et al, 2022 ; Farewell et al, 2020 ); psychological health symptoms were not screened by validated scales in three studies ( Dib et al, 2020 ; Ollivier et al, 2021 ; Jafree et al, 2021 ), and four studies reported the mean score for psychological health symptoms instead of prevalence ( Mayopoulos et al, 2021 ; McFarland et al, 2021 ; Shayganfard et al, 2020 ; Fernandes et al, 2021 ). Finally, 29 articles were included in the meta-analysis ( Loret de Mola et al, 2021 ; Pariente et al, 2020 ; Racine et al, 2021 ; Silverman et al, 2020 ; An et al, 2021 ; Basu et al, 2021 ; Bo et al, 2020 ; Boekhorst et al, 2021 ; Ceulemans et al, 2021 ; Ceulemans et al, 2020 ; Chrzan-Dętkoś et al, 2021 ; Fallon et al, 2021 ; Guvenc et al, 2021 ; Hamami et al, 2020 ; Hiiragi et al, 2021 ; Hui et al, 2021 ; Liang et al, 2020 ; Lorentz et al, 2020 ; Mariño-Narvaez et al, 2021 ; Molgora and Accordini, 2020 ; Oskovi-Kaplan et al, 2021 ; Ostacoli et al, 2020 ; Spinola et al, 2020 ; Stojanov et al, 2021 ; Suárez-Rico et al, 2021 ; Sun et al, 2020b ; Suzuki, 2022 ; Zanardo et al, 2020 ; Zeng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many parents and caregivers are also experiencing greater stress because of the lockdown and home schooling and increased time with their children has caused many to feel uncertain of their parental abilities, which is especially apparent in the group characterized by the following factors: motherhood, being single, having younger children, having a special needs child, and having many children (35). These factors combined are liable to lead to intra-family conflicts and, in some cases, family violence (36)(37)(38). The data show an increase in the number of children exposed to violence and witnessing domestic violence during the pandemic.…”
Section: Mental Health and Development In The Communitymentioning
confidence: 99%